Studying women entrepreneurs in the Indian context - SARGAM BAHL, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Women entrepreneurs are indeed an integral element of the world financial system today and played a critical job in it. For long-term growth in the economy and social advancement, the inclusion of women in entrepreneurship is crucial. While playing a significant part in Indian society, females’ economic potential has not yet been fully realized because of their inferior social position. This essay's major goal is to assess the situation of female entrepreneurs in the nation of India. It also focuses on the reasons why women choose to become businesses. In an effort to determine if the actions and policies done by the government of India to promote female entrepreneurs are adequate or not, an analysis of such policies and actions has also been made. Some recommendations are made to support the entrepreneurial drive in women on the foundation of this research